Evaluating the Effectiveness of QuillBot-Paraphraser in Improving Students’ Paraphrasing Skills: Students’ Points of View - Puspitasari, Ikke Meliana; Hartono, Hartono; Ekaningsih, Nur; Hidayati, Nani (Journal of Advanced Multidisciplinary Research, 2025)
Educational technology has developed very rapidly. Students use it as a means to improve learning and skills. One of the educational technologies related to writing in a foreign or second language is the QuillBot-Paraphraser. This research aims to evaluate the effectiveness of QuillBot-Paraphraser in improving students' paraphrasing skills and the advantages and disadvantages of this feature. This study adopted mix-method research design. The quantitative data was collected through questionnaire containing closed-ended questions and analyzed using SPSS, while qualitative data was collected using semi-structured interviews and analyzed thematically. Ninety students of the English Education and English Literature study program from two private universities in Semarang filled out questionnaires and ten of them were selected as respondents in semi-structured interviews. The results of quantitative data analysis show that QuillBot-Paraphraser is able to improve students' paraphrasing skills to a high level (M=4.13, SD=0.833). Respondents agreed that QuillBot-Paraphraser was effective in improving their paraphrasing skills. Differences in universities, study programs, and semesters had no effect on their opinions about the effectiveness of this tool. The semi-structured interview results show that QuillBot-Paraphraser is useful as a tool to help improve paraphrasing skills, provides fast and easy access, makes it easier to compose good and accurate paraphrased sentences, and enriches vocabulary. Apart from that, respondents in this study also stated that QuillBot-Paraphraser could make them lazy and dependent. In light of the findings, the study recommends that QuillBot-Paraphraser be used as a companion tool for writing activities, especially to improve paraphrasing skills.